Divided fates the state, race, and Korean immigrants' adaptation in Japan and the United States - Suzuki, Kazuko 1967- (Lanham Lexington Books, 2016)
"This book takes a cross-national and comparative approach, beyond American models, to examine how members of a single ethnic group adapt differently to distinct host societies. In her study of Korean immigrants to Japan and the United States, Suzuki finds that the state's mode of reception and its racialization of migrants determine adaptation patterns"--Provided by publisher.
A note on names -- Introduction: Cross-national comparison of immigrant adaptation -- Part I. Koreans in Japan -- Who are they and why did they come? -- Managing the multiethnic empire -- Survival in state-based politics -- Perpetual foreigners -- Socio-economic adaptation -- Community formation of the invisible minority -- Part II. Koreans in the United States : from a comparative perspective -- Beneficiaries of the Cold War -- Survival in a racial society -- Formation of the enclave community -- Conclusion: Toward a theory of cross-national comparison of immigrant adaptation -- Appendix A: Statistical data used in this study -- Appendix B: The 1993 Zainichi survey -- Appendix C: The 1995-1996 SSC survey.
Includes bibliographical references (pages 235-252) and index.
Keywords: Koreans -- Social conditions. -- Japan; Koreans -- Social conditions. -- United States; Immigrants -- Social conditions. -- Japan; Immigrants -- Social conditions. -- United States; Adjustment (Psychology) -- Japan; Adjustment (Psychology) -- United States; Social surveys -- Japan; Social surveys -- United States; Japan -- Race relations -- Political aspects; United States -- Race relations -- Political aspects